Combination of two different homozygote mutations in Pompe disease - Arslan, Alev; Poyrazoglu, Hatice Gamze; Kiraz, Aslihan; Ozcan, Alper; Isik, Halid; Ergul, Ayse Betuel; Torun, Yasemin Altuner (Wiley-Blackwell, 2016)
Pompe disease (OMIM no 232300) is an autosomal recessive inherited metabolic disorder, caused by glycogen accumulation in the lysosome due to deficiency of the lysosomal acid 03B1-glucosidase enzyme. Here we report the case of an 8-month-old girl of consanguineous Turkish parents, who was diagnosed with the infantile form of Pompe disease. Two different uncommon homozygote mutations (c.32-13T>G homozygote and c.1856G>A homozygote) were detected. The patient had a more progressive clinical course than expected. We emphasize the rare combination of genetic mutations in this Turkish family with Pompe disease.
Keywords: hypertrophic cardiomyopathy; infantile Pompe disease; novel mutation